Biased, Bitopic, Opioid-Adrenergic Tethered Compounds May Improve Specificity, Lower Dosage and Enhance Agonist or Antagonist Function with Reduced Risk of Tolerance and Addiction - Robert Root-Bernstein (MDPI AG, 2022)
This paper proposes the design of combination opioid-adrenergic tethered compounds to enhance efficacy and specificity, lower dosage, increase duration of activity, decrease side effects, and reduce risk of developing tolerance and/or addiction. Combinations of adrenergic and opioid drugs are sometimes used to improve analgesia, decrease opioid doses required to achieve analgesia, and to prolong the duration of analgesia. Recent mechanistic research suggests that these enhanced functions result from an allosteric adrenergic binding site on opioid receptors and, conversely, an allosteric opioid binding site on adrenergic receptors. Dual occupancy of the receptors maintains the receptors in their high affinity, most active states; drops the concentration of ligand required for full activity; and prevents downregulation and internalization of the receptors, thus inhibiting tolerance to the drugs. Activation of both opioid and adrenergic receptors also enhances heterodimerization of the receptors, additionally improving each drug's efficacy. Tethering adrenergic drugs to opioids could produce new drug candidates with highly desirable features. Constraints-such as the locations of the opioid binding sites on adrenergic receptors and adrenergic binding sites on opioid receptors, length of tethers that must govern the design of such novel compounds, and types of tethers-are described and examples of possible structures provided.